2013
DOI: 10.1080/08898480.2013.831698
|View full text |Cite
|
Sign up to set email alerts
|

A Pair-Approximation Model for Spatial Patterns in Tree Populations with Asymmetrical Resource Competition

Abstract: A pair-approximation model for the spatial dynamics of a height-structured tree population 10 is defined on a regular lattice where each site can be in one of three states: empty (gap site), occupied by an immature tree, and occupied by a mature tree. The nonlinearities are associated with resource competition effects of mature trees on immature ones (asymmetric competition) affecting the mortality of the latter but not their growth. The survival-extinction transition of the forest is expressed; the early dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In another study, a sapling species richness of only 21 % was found in gaps smaller than 50 m 2 (Hubbell et al, 1999). In these studies, the main causes of species diversity in gap regeneration probably were: i) less adult tree species at the gap edge of small gaps, or/and, ii) an early high degree of speciesselective self-thinning, due to intra and interspecific competition-induced mortality in small gaps, during the course of population development in tree community (Lepš & Kindlmann, 1987;Getzin, Wiegand, Wiegand, & He, 2008;García-Domingo & Saldana, 2013;Wehenkel, Brazão-Protázio, Carillo-Parra, Martínez-Guerrero, & Crecente-Campo, 2015), because of different seed production rate, dispersal, and vigour and shade tolerance of seedlings and saplings of different tree species (Canham, 1989). In contrast, the competition-induced mortality in the larger gaps was probably lower due to lower over story competition on understory gap regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a sapling species richness of only 21 % was found in gaps smaller than 50 m 2 (Hubbell et al, 1999). In these studies, the main causes of species diversity in gap regeneration probably were: i) less adult tree species at the gap edge of small gaps, or/and, ii) an early high degree of speciesselective self-thinning, due to intra and interspecific competition-induced mortality in small gaps, during the course of population development in tree community (Lepš & Kindlmann, 1987;Getzin, Wiegand, Wiegand, & He, 2008;García-Domingo & Saldana, 2013;Wehenkel, Brazão-Protázio, Carillo-Parra, Martínez-Guerrero, & Crecente-Campo, 2015), because of different seed production rate, dispersal, and vigour and shade tolerance of seedlings and saplings of different tree species (Canham, 1989). In contrast, the competition-induced mortality in the larger gaps was probably lower due to lower over story competition on understory gap regeneration.…”
Section: Discussionmentioning
confidence: 99%